Education for Married Women of Childbearing Age About Cervical Cancer through IVA Testing Behavior in the Gondrong Health Center Work Area - Albahra, Albahra; Dwi Lestari, Hernida (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
This research aims to teach Women Of Fertilizer Age about Cervical Cancer, to find out the behavior of Women Of Fertilizer Age who carry out IVA tests and to find out the relationship between the knowledge of Women Of Fertilizer Age and the behavior of IVA tests in the Gondrong Community Health Center Work Area in 2021. The research design used is a quantitative design. This research method uses correlation analysis, namely research that aims to find out whether there is a relationship and how close the relationship is and whether the relationship is meaningful or not. This research was conducted with a survey, using cross sectional research, namely research carrying out measurements or observations on several populations at the same time. The population in this study were married women of childbearing age in the Gondrong Community Health Center working area. With a total of 3990 people and the sample numbered 98. Knowledge of Women of Childbearing Age about Cervical Cancer in the Gondrong Community Health Center Work Area in 2021 was found from 98 respondents, more of whom were found to have less knowledge, namely 46 people (46.9%). The behavior of women of childbearing age who underwent an IVA test in the Gondrong Health Center Work Area in 2021 was found to be more likely than 98 respondents to have the behavior of not carrying out an IVA test, namely 68 people (69.9%). It is known that there is a relationship between knowledge of women of childbearing age and behavior of IVA tests in the Gondrong Health Center work area in 2021.